2018
DOI: 10.1136/bjophthalmol-2017-311294
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up patterns and associated risk factors after paediatric cataract surgery: observation over a 5-year period

Abstract: Curve of loss to follow-up is logarithmic in children undergoing paediatric cataract surgery. Age at surgery and low economic status are the most important factors associated with poor follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…The study by Chougule and associates has reported a loss of follow-up from 85% at 1-month postsurgery to 52% at the end of 1 year 19. In our study, despite regular reminders for follow-ups through telephone calls and text messages, the rate of follow-ups dropped from almost 100% on the first postoperative day to 50% at 6 months.…”
Section: Discussioncontrasting
confidence: 71%
“…The study by Chougule and associates has reported a loss of follow-up from 85% at 1-month postsurgery to 52% at the end of 1 year 19. In our study, despite regular reminders for follow-ups through telephone calls and text messages, the rate of follow-ups dropped from almost 100% on the first postoperative day to 50% at 6 months.…”
Section: Discussioncontrasting
confidence: 71%
“…has suggested that age at surgery and low socioeconomic status are the most important factors associated with poor follow-up. [ 30 ] The poor outcome in our cohort could be due to delayed presentation (43%, n = −151), amblyopia due to the unilateral nature of cataract (42%, n = 147), and other comorbid factors like strabismus 32%, nystagmus 16%, and surgical aphakia 27% ( n = 147). We believe that timely follow-up and appropriate interventions could have addressed a few of these, such as coexisting amblyopia (primarily deprivational but possibly also strabismic and anisometropic amblyopia in aphakia) by appropriate refractive correction and early institution of amblyopia therapy.…”
Section: Discussionmentioning
confidence: 99%
“…50% of patients showed improvement, according to Lai et al 22 . According to Magnusson et al, 52% of children had better vision after surgery 23 . In first month of the follow-up period; no improvement in visual acuity was seen, but in later follow-ups, the majority of patients had good vision with a mean log MAR value of 0.5.…”
Section: Discussionmentioning
confidence: 99%